The Implementation Of The Storytelling Method To Enhance Early Childhood Languange Development - Sindy Gambella Bessie; Noldiana Nompetus; Restimar Tanti Abanat; Feni Sefniarti Kase; Sheryl Nathasya Siktimu; Fredericksen Victoranto Amseke (Jurnal E-MAS (Edukasi dan Pembelajaran Anak Usia Dini), 2026)
Background: Language development is a fundamental aspect of early childhood growth that plays an essential role in supporting children's communication skills, vocabulary acquisition, and social interaction. However, in classroom practice, some children still show limited vocabulary, low speaking confidence, and difficulty expressing ideas. Objective: This study aimed to investigate the effect of the storytelling method on the language development of children aged 3–4 years at TK Cemara Liliba. Method: A quantitative research design was employed using a purposive sampling technique involving 20 children. Data were collected through structured observation sheets and questionnaires, and analyzed using simple linear regression with SPSS. Results: The findings revealed that the storytelling method had a positive and significant effect on children's language development, contributing 35.4% (R² = 0.354), while 64.6% was influenced by other external and internal factors. Novelty: This study provides empirical evidence from an authentic early childhood setting that storytelling enhances children's active participation, listening comprehension, vocabulary enrichment, and expressive speaking skills when delivered through interactive and engaging activities. Conclusion: Storytelling is an effective instructional strategy to support early childhood language development and should be implemented consistently with teacher creativity and supportive learning environments for optimal developmental outcomes in early childhood education contexts settings.